A impulse response for a LTI system is given by:

$$h[n]=\left(\frac{2}{3}\right)^n u[n]+2 \left(\frac{1}{5}\right)^n u [n]$$

and if the putput for the system is given by:

$$y[n]= \left(\frac{1}{3}\right)^n u [n] $$

  • What is the input in the $z$-domain ($X(z)$)?
  • And what is the output in the time-domain ?

I'm not sure what is the correct procedure for solving this type of problem. Can you just simply transform $y[n]$ into $Y(z)$ and then solve for $X(z)$?

$$\frac{Y(z)}{X(z)}=\frac{3-\frac{23}{12}z^{-1} }{\left(1-\frac 23z^{-1}\right)\left(1-\frac 15z^{-1}\right) }$$

Then I replace $ Y(z)$ with $\frac{1}{1-1/3z^{-1}}$ and then I isolate $ X(z)$.

$$\frac{\frac{1}{1-\frac 13z^{-1}}}{X(z)}=\frac{3-\frac{23}{12}z^{-1} }{\left(1-\frac 23z^{-1}\right)\left(1-\frac 15z^{-1}\right)}.$$

Then I get $X(z)=\frac{6z^-2-39z^{-1}+45}{23z^{-1}-11z^{-1}+135}$ and then I transform it into a sequence in the time domain.

Is it right? or is there a better method for solving this.

  • $\begingroup$ please look at my answer to see your mistake... $\endgroup$
    – Fat32
    Commented Jun 29, 2016 at 21:34

2 Answers 2



$$Y(z) = H(z)X(z)$$ therefore $$X(z)=\frac{Y(z)}{H(z)}$$

Now, $$y[n]=\big(\frac{1}{3}\big)^n u[n] \longleftrightarrow Y(z)=\frac{1}{1-\frac{1}{3}z^{-1}}$$ and $$h[n]=\big(\frac{2}{3}\big)^n u[n] + 2\big(\frac{1}{5}\big)^n u[n] \longleftrightarrow H(z)=\frac{1}{1-\frac{2}{3}z^{-1}}+\frac{2}{1-\frac{1}{5}z^{-1}}$$

will you please perform the necessary arithmetic... to find $$X(z) = \frac{\frac{1}{1-\frac{1}{3}z^{-1}}}{\frac{1}{1-\frac{2}{3}z^{-1}}+\frac{2}{1-\frac{1}{5}z^{-1}}}$$

Lets also display the further steps: \begin{align} H(z) &=\frac{1}{1-\frac{2}{3}z^{-1}}+\frac{2}{1-\frac{1}{5}z^{-1}} = \frac{3-\frac{23}{15}z^{-1}}{(1 - \frac{2}{3}z^{-1})(1-\frac{1}{5}z^{-1})} = \frac{3(1-\frac{23}{45}z^{-1})}{(1 - \frac{2}{3}z^{-1})(1-\frac{1}{5}z^{-1})}\\ Y(z) &=\frac{1}{1-\frac{1}{3}z^{-1}}\\ \\ X(z) &= Y(z)/H(z) = \frac{1}{1-\frac{1}{3}z^{-1}} \frac{(1 - \frac{2}{3}z^{-1})(1-\frac{1}{5}z^{-1})}{3(1-\frac{23}{45}z^{-1})}\\ \\ X(z) &= \frac{\frac{1}{3}(1 - \frac{2}{3}z^{-1})(1-\frac{1}{5}z^{-1})}{(1-\frac{1}{3}z^{-1})(1-\frac{23}{45}z^{-1})} ~~~~~~\scriptstyle{\text{Performing partial fraction expansion on X(z), results in:}}\\ \\ X(z) &= 0.26087 + \frac{0.25}{1-\frac{1}{3}z^{-1}} + \frac{-0.17754}{1-\frac{23}{45}z^{-1}} ~~~~\scriptstyle{\text{Transform each term back into time by a table...}}\\ \\ x[n] &= 0.26087 \cdot \delta[n] + 0.25 \big(\frac{1}{3}\big)^n u[n] - 0.17754 \big(\frac{23}{45}\big)^n u[n] \\ \end{align}

Sorry that the partial fraction expansion resulted in numeric format, rather than algebraic...


I haven't checked your solution, but the procedure appears correct:



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.